More Complications Occur in Macrolide-Resistant than in Macrolide-Sensitive Mycoplasma pneumoniae Pneumonia - Zhou, Yunlian (American Society for Microbiology, 2014)
We sought to understand the situation of macrolide-resistant genotypes of Mycoplasma pneumoniae, and analyze the relationship between macrolide-resistant genotypes and clinical manifestations of Mycoplasma pneumoniae pneumonia (MPP). Full-length sequencing of the 23S rRNA gene of M. pneumoniae was performed in 235 nasopharyngeal aspirates (NPAs) from children with MPP. We also retrospectively compared the clinical characteristics of macrolide-resistant (MR) M. pneumoniae infections and macrolide-sensitive (MS) M. pneumoniae infections. A total of 206 patients had point mutations in the M. pneumoniae 23S rRNA gene, and these patients are referred to as MR patients. The remaining 29 patients without point mutations are referred to as MS patients. Among 206 MR patients, 199 (96.6%) had A2063G mutations, 6 had A2063T mutations, and the remaining patients had an A2064G mutation. Among the clinical manifestations, we found that the median fever durations were 8 days (range, 0 to 42 days) and 6 days (0 to 14 days) (P < 0.01), the median hospitalization durations were 8 days (2 to 45 days) and 6 days (3 to 16 days) (P < 0.01), and the median fever durations after macrolide therapy were 5 days (0 to 42 days) and 3 days (0 to 10 days) (P < 0.01), respectively, in the MR and MS groups. We also found that the incidence of extrapulmonary complications in the MR group was significantly higher than that in the MS group (P < 0.05). Moreover, the radiological findings were more serious in the MR group than in the MS group (P < 0.05). The increasing prevalence of MR M. pneumoniae has become a significant clinical issue in the pediatric patients, which may lead to more extrapulmonary complications and severe clinical features and radiological manifestations.